2008
DOI: 10.1016/j.brainres.2007.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Experience-based priming of body parts: A study of action imitation

Abstract: Abstract:Two important dimensions of action are the movement and the body part with which the movement is effected. Experiment 1 tested whether automatic imitation is sensitive to the body part dimension of action. We found that hand and foot movements were selectively primed by observation of a corresponding, task-irrelevant effector in motion.Experiment 2 used this body part priming effect to investigate the role of sensorimotor learning in the development of imitation. The results showed that incompatible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

5
5

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 67 publications
10
86
1
Order By: Relevance
“…The results of the transfer test are consistent with those of human studies showing that incompatible sensorimotor experience-performing one action while observing an alternative action-can abolish [4,24] and reverse automatic imitation [25,26]. For example, using TMS, Catmur et al [25] found that, prior to training, observation of index finger movement yielded larger TMS-induced motor evoked potentials (MEPs) in an index finger muscle than in a little finger muscle, and vice versa for observation of little finger movement.…”
Section: Discussionsupporting
confidence: 85%
“…The results of the transfer test are consistent with those of human studies showing that incompatible sensorimotor experience-performing one action while observing an alternative action-can abolish [4,24] and reverse automatic imitation [25,26]. For example, using TMS, Catmur et al [25] found that, prior to training, observation of index finger movement yielded larger TMS-induced motor evoked potentials (MEPs) in an index finger muscle than in a little finger muscle, and vice versa for observation of little finger movement.…”
Section: Discussionsupporting
confidence: 85%
“…Twenty-four hours after training of this kind, responding in incompatible trials was as fast as responding in compatible trials. Gillmeister et al (2008) demonstrated a comparable reduction in automatic imitation of hand and foot actions following incompatible sensorimotor experience, while Catmur et al (2007) showed that, in the case of little-and index-finger abduction movements, incompatible sensorimotor experience can reverse automatic imitation, producing a systematic, involuntary tendency to counter-imitate the observed action (see below). On the basis of associative learning theory, incompatible sensorimotor training would be expected to establish new, non-matching vertical associations, e.g.…”
Section: Sensorimotor Learning and Imitationmentioning
confidence: 98%
“…The imitation treatment stimuli comprised images of the resting and endpoint positions of hand and foot lifting actions (Gillmeister, Catmur, Liepelt, Brass, & Heyes, 2008). Both hand and foot were present in the resting position, centered vertically on the screen, on every trial.…”
Section: Stimulimentioning
confidence: 99%